Dampak Andrografolid dan Dua Jenis Insektisida Sintetik sebagai Penghambat Makan Nephotettix virescens, terhadap Transmisi Virus Tungro - I Nyoman Widiarta; Muhammad Muhsin; Dede Kusdiaman (Jurnal Perlindungan Tanaman Indonesia, 1998)
The effect of andrographolide and two synthetic insecticides of pymetrozine and imidacloprid, an antifeedant against N. virescens (Distant), to the rice virus transmission were tested using test tube inoculation method in the green house under natural photoperiod and average temperature of 28.5oC. The root of tungro diseased plant were soaked for 24 hours into tested materials before acquisition feeding to test virus acquisition inhibition, while root of rice seedlings were soaked into tested material for 24 hours before inoculation feeding to test virus inoculation inhibition. The results of studies showed that andrographolide, pymetrozine, and imidacloprid significantly reduced virus acquisition and virus inoculation by N. virescens. Pymetrozine and andrographolide treatments to the tungro diseased plants at concentration of 20 ppm significantly reduced proportion of viruliferous vector to become 17% in average. The increasing concentration into 40 ppm of both materials did not significantly reduce proportion of viruliferous vector. Imidacloprid at concentration of 0.01 and 0.02 ppm, completey inhibited feeding acquisition. Pymetrozine and andrographolide treatment at concentration of 20 ppm to the rice seedlings reduced significantly virus transmission by N. virescens to become 69% in average. The increasing concentration of pymetrozine up to 40 ppm did not reduce virus transmission rate. Imidacloprid at concentration of 0.01 ppm and 0.02 ppm reduced virus transmission to become 25% and 39%, respectively. It was concluded that imidacloprid was the most effective antifeedant reducing virus transmission by N. virescens among tested chemicals.